Patent System in The Control of Science and Technology in Indonesia: Intellectual Property Rights (IPR) and Development - Bintang Arbakmis; Ferdiyan Ganesha; Budi Agus Riswandi (Journal of Islamic Law El Madani, 2024)
Intellectual Property Rights (IPR) is one form human wealth resources that are intangible and are the result of human intellectual ability mindset. Basically, Property Rights Intellectual Property Rights (IPR) is an exclusive right given to someone which has produced works, arises as a result of intellectual abilities humans in various fields who produce a process or product which is beneficial to humans and can be enjoyed economically by man himself. The aim of this research is to determine the patent system in mastering science and technology in Indonesia. The research method used is normative juridical with analytical descriptive research specifications. The results of the research are that the government must have a good patent information service system for patents that have become public domain, so that when the patent expires, the technology that has become public domain can be widely used by the Indonesian people. Law enforcement and patent protection are very important to create a fair and competitive business. This not only helps innovation and investment, but also protects intellectual property rights that greatly influence Indonesia's technology and economy. By collaborating between sectors and protecting intellectual property rights, Indonesia can continue to progress in the future